For whom does the hen cackle? The function of postoviposition cackling - Pizzari, T; Birkhead, T (2001)
In birds, the time immediately after oviposition has been assumed to be particularly favourable for an insemination to fertilize eggs. Based on this assumption, Thornhill (1988, Verhandlungen der Deutschen Zoologischen Gesellschaft, 81, 145-154) suggested that a particular vocalization, the postoviposition cackle, of female fowl, Gallus gallus, signalled a peak in fertility, which incited male sexual behaviour and resulted in females copulating with the most dominant males. It may therefore benefit females by indirectly selecting for competitive copulation partners. We tested this hypothesis in a free-ranging population of feral fowl. Contrary to the hypothesis, we found that: (1) postoviposition cackling was associated with a significantly lower probability of a female obtaining a copulation; and (2) males did not respond any differently to the experimental playback of the postoviposition cackling and a control call. These results are consistent with the period immediately after oviposition being an unfavourable time for an insemination to fertilize eggs. One function of postoviposition cackling may thus be to avoid the costs of sexual harassment by signalling to males a particularly unsuitable time for fertilization. © 2001 The Association for the Study of Animal Behaviour.